LANGUAGE LEARNING STRATEGIES OF HIGH PROFICIENCY STUDENTS IN THEIR ORAL PRESENTATION AT ENGLISH LANGUAGE EDUCATION OF PGRI RONGGOLAWE UNIVERSITY TUBAN - Panggabean, Christina I.T.; Kesuma, Ingelia (OKARA: Jurnal Bahasa dan Sastra, 2017)
This study is intended to describe 1) the language learning strategies used by male and female students with high speaking performance in their oral presentation and 2) their reasons of using certain language learning strategies. This study used descriptive qualitative method. The subject of the study were ten high proficiency students consisting of four male students and six female students. Questionnaire and interview were used to collect the data. The data from the questionnaire and the interview were analyzed descriptively. The result indicated that all of the students from high proficiency level used all learning strategies, including memory strategy, cognitive strategy, compensation strategy, metacognitive strategy, affective strategy, and social strategy. The students were categorized as medium users of language learning strategy. High proficiency male students used compensation strategy (3.85) the most frequently, followed by meta-cognitive strategy (3.63) and social strategy (3.37). Meanwhile, high proficiency female students used cognitive strategy (4.02) the most frequently, followed by compensation strategy (3.77) and metacognitive strategy (3.72). Both male and female students had some different and similar reasons of using certain language learning strategies for their oral presentation task.